Multiomics analysis reveals microbial diversity and activity through spontaneous fermentation of Theobroma cacao - Ynara da Costa Fonseca; Celina Eugenio Bahule; Hector Herrera; Luiza Helena da Silva Martins; Alessandra Santos Lopes; Juliana Silva Cassoli; Felipe Costa Trindade; Isa Rebecca Chagas da Costa; Paulo Henrique de Oliveira Costa; Guilherme Oliveira; Rafael Borges da Silva Valadares (Heliyon, 2024)
To gain insight into the active microbiota during spontaneous fermentation of Theobroma cacao L., this study assessed protein diversity during 120 h using a combined metabarconding and metaproteomics approach. During the first days of fermentation, most of the peptides were associated with T. cacao and yeast (0–72 h). Peptides associated with bacteria became more abundant after 72 h of fermentation, coinciding with a decrease in peptides associated with cocoa (96–120 h). In addition to the known microorganisms involved in fermentation, such as Saccharomyces, Lactobacillus and Acetobacter, novel genera were also metabolically active, including Microvirga, Inquilinus, Candolleomyces and Lasiodiplodia.. The results showed a consistency in the main genera detected by both techniques, but the identification of unexplored genera such as Inquilinus, Microvirga, Cyphellophora and Ashbya gossypii, among others, suggests that this omics approach needs to be used together for more comprehensive results on spontaneous fermentation. In conclusion, studies combining techniques such as metabarcoding and metaproteomics should be considered in fermentation studies, as a single technique would result in omissions regarding the activity of certain microorganisms that may be important for the course of spontaneous fermentation.